Polypropylene-based eco-composites filled with agricultural rice hulls waste - Dimzoski, B. (Array, 2009)
Summary: In this workthe properties of rice-hull-filled polypropylene (PP) composites were investigated with the purpose of enhancing adhesion between the polymer and the filler through the addition of w = 5 % PP-grafted-MA (CA). Composites containing w = 20 and 30 % rice hulls (RH), as well as composites with a certain amount of PP matrix substituted with a coupling agent, were prepared by extrusion and compression moulding. The composites’ mechanical properties were investigated through tensile and fracture tests at low and high strain rate, using the concept of linear elastic fracture mechanics. Introduction of rice hulls in the PP matrix resulted in a decreased stress at peak, together with increase of composites tensile modulus (EPP = 1013 MPa, EPP/RH (ζ = 0.70:0.30) = 1690 MPa) and modulus in flexure. Introduction of w = 5 % PP-g-MA caused 6 % and 12 % improvement in the composite tensile strength, respectively for the PP composites with w = 20 and 30 % rice hulls. Modulus in flexure for the composite PP/RH/CA (ζ = 0.65:0.30:0.05) reached Ef = 1646 MPa, which was an improvement of 52 % when compared to pure polypropylene. Kc and Gc values were determined for PP and PP-based composites. Thermal stability of PP was slightly improved by adding rice hulls